Role of MRI in the Diagnosis and Characterization of Adnexal Masses in a Tertiary Hospital of Central Nepal - Prasad, V.Natraj (Journal of College of Medical Sciences-Nepal, 2025)
Background Adnexal masses represent a wide spectrum of gynecological conditions, ranging from benign cysts to malignant ovarian tumors. Accurate diagnosis and characterization are critical for clinical decision-making, including surgical planning, fertility preservation, and oncological referral. Magnetic Resonance Imaging (MRI), with superior soft-tissue contrast, multiplanar capability, and functional imaging techniques, offers improved characterization of adnexal masses. The objective of this study was to evaluate the diagnostic role of MRI in detecting and characterizing adnexal masses. Methods A hospital-based cross-sectional study was conducted among 80 female patients with adnexal masses identified on USG at the department of Radiology of College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. All patients undergo MRI evaluation followed by surgical excision and histopathological confirmation. Data were entered and analyzed using SPSS-20. P-value<0.05 was considered as statistically significant. Results Among all patients, the mean±SD of age was 38.42±6.28 years. Most of the patients (25%) were in 30-39 years with 62.5% premenopausal. Histopathology revealed 68.8% benign and 31.2% malignant lesions. MRI demonstrated sensitivity 85%, specificity 72%, PPV 78%, NPV 80%, and overall accuracy 77.5%. Restricted diffusion, solid components, peritoneal deposits, and contrast enhancement were significantly associated with the type of masses (p < 0.05). Conclusions MRI is a reliable imaging modality for differentiating benign from malignant adnexal masses, identifying key imaging markers, and guiding clinical management. Integration of MRI into diagnostic pathways improves patient care and reduces unnecessary interventions.